Case report and literature review: An intrahepatic sewing needle in a child - Shi, Hao; Lv, Zhibao; Xu, Weijue; Sheng, Qingfeng; Huang, Xiong; Xu, Ting (Frontiers in Pediatrics, 2023)
Background: Presence of intrahepatic foreign bodies is a rare occurrence at the emergency department. Normally, foreign bodies reach the liver through migration. Incidence is lower among children than among adults, and the circumstances of children are often different. We report a 19-month-old boy with a sewing needle in the liver and review the previous reports of intrahepatic sewing needle in the PubMed database from the last three decades. Case presentation: A 19-month-old boy was transferred to our center from a local hospital with a presentation of intermittent cough and rhinorrhea. A chest radiograph to exclude pulmonary disease revealed an incidental finding of a high-density shadow in the hepatic region. On admission, the boy had no gastrointestinal symptoms. Abdominal physical examinations were unremarkable. His mother, a worker in a textile factory, denied any history of trauma. Abuse was excluded based on investigation. Preoperative routine test results were normal. Contrast-enhanced computed tomography (CT) revealed that the sewing needle was located in hepatic segment IV and the tip had close relationship with intrahepatic portal vein. Initially, laparoscopy was performed without success. We eventually converted to laparotomy to completely remove the rusty sewing needle. The patient resumed feeding soon after the operation and was discharged in a few days. Conclusions: Intrahepatic sewing needle has high incidence among boys and developing countries. Combined with contrast-enhanced CT, knowledge of the pediatric patient's family background and medical history would help judge the route of entry and determine the management and surgical strategy. Laparoscopic procedure is not suitable for rusty sewing needles.